2017
DOI: 10.4049/immunohorizons.1700001
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Does Not Exacerbate the Protumorigenic Systemic Environment in Sarcoma Subjects

Abstract: Sarcomas are a rare but fatal tumor type that accounts for <1% of adult solid malignancies and ~15% of childhood malignancies. Although the use of immunotherapy is being actively investigated for other solid tumors, advances in immunotherapy for sarcoma patients are lacking. To better understand the systemic immune environment in sarcoma patients, we performed a detailed multiplex analysis of serum cytokines, chemokines, and protumorigenic factors from treatment-naive subjects with localized, high-grade sarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Histopathologically, sarcomas are classified as either bone or soft tissue sarcomas [ 3 ]. To date, the etiology of sarcomas is not well characterized; however, their incidence appears to be associated with heredity [ 4 ], viral infection [ 5 ], trauma [ 6 ], environmental factors [ 7 ], and exposure to radiation [ 8 ]. Compared with other cancers, the degree of malignancy of sarcomas is relatively high [ 9 ], and hematogenous metastasis can spread to various organs, such as lung, brain, liver, and bone [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, sarcomas are classified as either bone or soft tissue sarcomas [ 3 ]. To date, the etiology of sarcomas is not well characterized; however, their incidence appears to be associated with heredity [ 4 ], viral infection [ 5 ], trauma [ 6 ], environmental factors [ 7 ], and exposure to radiation [ 8 ]. Compared with other cancers, the degree of malignancy of sarcomas is relatively high [ 9 ], and hematogenous metastasis can spread to various organs, such as lung, brain, liver, and bone [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our prior studies using an orthotopic murine renal cancer model revealed that immune dysfunction was exacerbated in mice with diet-induced obesity [9,11]. However, despite numerous pre-clinical results indicating that obesity promotes tumor progression via multiple detrimental effects on the immune system, our retrospective examination of human sarcoma subjects revealed that obesity had surprisingly limited effects on plasma cytokine and chemokine profiles, leading us to conclude that obesity, as measured by BMI, did not exacerbate the pro-tumorigenic systemic environment in treatment-naive individuals with sarcoma [16].…”
Section: Introductionmentioning
confidence: 64%
“…Some studies showed that excessive amounts of adipose tissue promoted resistances of leukemic cells to chemotherapy and facilitated tumor spread [21,23]. In contrast, in sarcoma patients, obesity did not appear to exacerbate the protumorigenic environment and aggravate a predisposition to tumor progression [24]. A recent case-control study suggested that obesity during childhood cancer treatment might be associated with increased risk for SMNs [25].…”
Section: Discussionmentioning
confidence: 99%